ANALISIS MINAT BELAJAR MATEMATIKA SISWA SEKOLAH DASAR MELALUI METODE BLENDED LEARNING DITINJAU DARI PERINGKAT DAN GENDER - Umar Umar; Andi Kaharuddin; Arif Widodo (COLLASE (Creative of Learning Students Elementary Education), 2021)
Abstract This study aims to analyze and describe the positive effect of the blended learning method on the learning interest of elementary school students in terms of rank and gender. The research subjects consisted of 4 students. This type of research is a mixed methods research with explorary sequential design. Data were collected using observation instruments, interviews and learning outcomes tests. The data analysis used is narrative exploration and descriptive analysis. The results showed that MA subjects with high rankings with male gender had very high interest in learning from the application of blended learning methods, high-ranking SA subjects with female gender had high learning interests from applying blended learning methods, AH subjects with low ratings with the male gender has a high interest in learning from the application of the blended learning method, the low-ranking RA subject with the female gender has a very low interest in learning from the application of the blended learning method. Keywords: Interest in Learning, Blended Learning, Ranking, Gender AbstrakPenelitian ini bertujuan untuk menganalisis dan mendeskripsikan pengaruh positif metode blended learning terhadap minat belajar siswa sekolah dasar ditinjau dari peringkat dan gender. Subjek penelitian terdiri dari 4 siswa. Jenis penelitian ini adalah penelitian campuran dengan desain explorary sequential. Data dikumpulkan menggunakan instrument observasi, wawancara dan tes hasil belajar. Analisis data yang digunakan adalah eksplorasi naratif dan analisis deskriptif. Hasil penelitian menunjukkan subjek MA yang berperingkat tinggi dengan jenis kelamin laki-laki memiliki minat belajar sangat tinggi dari penerapan metode blended learning, subjek SA yang berperingkat tinggi dengan jenis kelamin perempuan memiliki minat belajar tinggi dari penerapan metode blended learning, subjek AH yang berperingkat rendah dengan jenis kelamin laki-laki memiliki minat belajar tinggi dari penerapan metode blended learning, subjek RA yang berperingkat rendah dengan jenis kelamin perempuan memiliki minat belajar sangat kurang dari penerapan metode blended learning. Kata Kunci: Minat Belajar, Blended Learning, Peringkat, Gender